PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA EMITEN YANG TERGABUNG DALAM JAKARTA ISLAMIC INDEX - Nurmila Dewi; Azizah Mardilla (Politeknik Negeri Lhokseumawe, 2016)
This research aims to determine the effect of the financial performance of the stock price on issuers incorporated in Jakarta Islamic Index. Sharia stocks in Jakarta Islamic Index are corporations stocks while are in operation not contradiction with Islamic Sharia, either in forms of their products or managements. This research was conducted using secondary data. Sampling technique used was purposive sampling. Sample in this research is consistenly listed companies listing in Jakarta Islamic Index during the period 2010-2014, in order to obtain a sample of 10 (ten) companies. The analytical method used is multiple regression analysis.The result simultaneously showed that Return On Equity, Earning Per Share, Debt to Equity Ratio, and Net Profit Margin significant effect on stock prices. The result showed that partially Return On Equity positive and significant effect on stock prices, Earning Per Share positive and significant effect on stock prices, Debt to Equity Ratio negative and have no significant effect on stock prices, and Net Profit Margin negative and significant impact on stock prices.Keyword: Return On Equity, Earning Per Share, Debt to Equity Ratio, Net Profit Margin, Stock Prices.